Selective oxidation of glycerol on morphology controlled ceria nanomaterials. Issue 9 (18th April 2019) - Tinoco, Miguel; Fernandez-Garcia, Susana; Villa, Alberto; Gonzalez, Juan M.; Blanco, Ginesa; Hungria, Ana B.; Jiang, Lei; Prati, Laura; Calvino, Jose J.; Chen, Xiaowei
Abstract : It is reported, for the first time, that morphology controlled ceria without any addition of other metal exhibits catalytic activity for selective oxidation of glycerol. Moreover, development of 111 nanofacets plays an important role in both activity and selectivity. Abstract : Ceria has attracted great interest in heterogeneous catalysis due to its facile exchange between Ce 3+ and Ce 4+ . In particular, in this work it is reported, for the first time, that morphology controlled ceria without any addition of other metal exhibits catalytic activity for the selective oxidation of glycerol. Singularly, ceria nanorods present the highest catalytic activity among all tested materials, which can be attributed to their highest surface area. Nevertheless, surface crystallography plays a key role in determining the catalytic activity and selectivity of these nanocatalysts, as proven by TEM, Raman and XPS analyses. In particular, the development of 111 ceria nanofacets on ceria nanocubes strongly affects both activity and selectivity in the selective oxidation of glycerol. On the other hand, Ce 3+ surface content cannot be discarded as an important factor in the catalytic activity of ceria nanoparticles for this specific redox reaction.